2006
DOI: 10.1111/j.1460-9568.2005.04543.x
|View full text |Cite
|
Sign up to set email alerts
|

An identified central pattern‐generating neuron co‐ordinates sensory‐motor components of respiratory behavior in Lymnaea

Abstract: Defining the attributes of individual central pattern-generating (CPG) neurons underlying various rhythmic behaviors are fundamental to our understanding of how the brain controls motor programs, such as respiration and locomotion. To this end, we have explored a simple invertebrate preparation in which the neuronal basis of respiratory rhythmogenesis can be investigated from the whole animal to a single cell level. An identified dopaminergic neuron, termed right pedal dorsal 1 (RPeD1), is a component of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…L. stagnalis has been used primarily to study the neural mechanisms underlying feeding and respiratory behaviours (Vavoulis et al, 2007;Bell et al, 2007;Haque et al, 2006), as well as a variety of questions on learning and memory (Martens et al, 2007), neural plasticity and cell biology (Dunn and Syed, 2006;Jimenez et al, 2006). While H. trivolvis has also contributed in some of these areas (Murphy, 2001;Torreano et al, 2005), it has become a particularly good model to address a broad range of developmental questions because of the advantageous morphological and biomechanical properties of its egg mass.…”
Section: Introductionmentioning
confidence: 99%
“…L. stagnalis has been used primarily to study the neural mechanisms underlying feeding and respiratory behaviours (Vavoulis et al, 2007;Bell et al, 2007;Haque et al, 2006), as well as a variety of questions on learning and memory (Martens et al, 2007), neural plasticity and cell biology (Dunn and Syed, 2006;Jimenez et al, 2006). While H. trivolvis has also contributed in some of these areas (Murphy, 2001;Torreano et al, 2005), it has become a particularly good model to address a broad range of developmental questions because of the advantageous morphological and biomechanical properties of its egg mass.…”
Section: Introductionmentioning
confidence: 99%
“…Such a preparation provides a valuable model system to elucidate the nature of ionotropic ion channels that shape the bio-electrical behavior of RPeD1. It has been shown that, in the isolated CNS, RPeD1 frequently exhibits a spontaneously occurring respiratory discharge, similar to that recorded in ''semiintact preparations'' following direct current injection or mechano-chemical stimulation of the neuron (Bell et al 2007;Haque et al 2006;Holden et al 1982;Inoue et al 1996Inoue et al , 2001McComb et al 2003). Such spontaneous activity depends on neurotransmitter release from yet to identify presynaptic terminals.…”
Section: Isolated Brain Preparationsmentioning
confidence: 71%
“…The onset of patterned respiratory activity is controlled by both excitatory and inhibitory inputs mainly conveyed to RPeD1 from the pneumostome area (Bell et al 2007;Haque et al 2006;Inoue et al 2001;Lukowiak et al 2006;McComb et al 2003). Strikingly, this behavior can undergo a dramatic operant conditioning and the resulting changes (i.e., associative learning) be consolidated into both intermediateand long-term memory McComb et al 2005;Spencer et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations